2018
DOI: 10.1002/cbdv.201700550
|View full text |Cite
|
Sign up to set email alerts
|

Three New Indole Diketopiperazine Alkaloids from Aspergillus ochraceus

Abstract: Asperochramides A - D (1 - 4), a new natural product and three new indole diketopiperazine alkaloids, along with seven known analogs (5 - 11), were isolated from the ethyl acetate extract of Aspergillus ochraceus. Their structures were elucidated by extensive spectroscopic analyses, ECD calculation, and single-crystal X-ray diffraction analysis. Compounds 3 and 4 represent a rare group of indole diketopiperazine alkaloid with a 3-hydroxyl-2-indolone moiety. The in vitro anti-inflammatory effects of compounds 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…Additionally, the configuration of the C‐8/C‐9 double bond and C‐12 were shown to be ( R ) and ( S ), respectively . Clearly, the isopentenylation of the benzene ring or indole ring and the oxidoreduction and sulfuration of diketopiperazine ring resulted in diversities of the structures . Research on the preliminarily cytotoxic activities of compounds and fractions showed that the cytotoxic effects of Fr.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the configuration of the C‐8/C‐9 double bond and C‐12 were shown to be ( R ) and ( S ), respectively . Clearly, the isopentenylation of the benzene ring or indole ring and the oxidoreduction and sulfuration of diketopiperazine ring resulted in diversities of the structures . Research on the preliminarily cytotoxic activities of compounds and fractions showed that the cytotoxic effects of Fr.…”
Section: Discussionmentioning
confidence: 99%
“…4 Herein, we report the isolation of a new congener, Amoenamide B ( 1 ), along with Asperochramide A ( 2 ), which was isolated from Aspergillus ochraceus (cgmcc 3.6281), recently. 5…”
Section: Introductionmentioning
confidence: 99%
“…The EtOAc layer (7.0 mg) was concentrated in vacuo and then identified as 2-(2-hydroxyethyl) phenol. 1.5 Biological Assays 1.5.1 Anti-inflammatory Activity Anti-inflammatory activity of the new compounds was evaluated using the ELISA with indomethacin and dexamethasone serving as the positive controls [23] . RAW 264.7 cells were cultured in DMEM (HyClone, Logan, USA) supplemented with 10% heat inactivated fetal bovine serum (FBS) (HyClone) at 37°C in a humidified atmosphere with 5% CO 2 .…”
mentioning
confidence: 99%